Effet du jeun de ramadan chez les femmes diabétiques ménopausées sous thérapie aux metformine - Bouchachi Aichouche, Lamis; Bouchebbat, Souaad (My University, 2021)
Ramadan represents the sacred month of the year when muslims are supposed to refrain from eating, drinkin and having sex from sunrise to sunset. This monthprovides an excellent research model for studing changes in eating habits and their consequences on change on wheight status as well as fasting metabolism in people with type 2 diabetes. Twelve (12) diabetic women, aged 54 to over 70 years, on oral anti-diabetic with metformine were included in the study. The measurements and controls carried out in patients during the 15th day of ramadan and 1 month after ramadan concerned (glycemia, HbA1c, triglycerides, cholesterol, LDL-c, HDL-c and urine chemistry). The results underwent a single – factor block- factor variance analysis and a comparison of two-point means according to the Newman and Keuls test. The young of ramadan seems to improve blood sugar levels in postmenopausal diabetic women not significantly, but it turns out to alter the plasma lipid balance as well as the level of HbA1c. Moreover, the experiment revealed that the patients showed no hypoglycemia or hyperglycemia and no renal dysfunction proving to prevent them from fasting.
Keywords: type 2 diabetes ; metformine ; menopause ; ramadan ; fasting ; parameetrization biochemical.